Optimization of solar photovoltaic and diesel generator hybrid system - Suwal, Puskar (Journal of Science and Engineering, 2014)
The techno-economic viability of a hybrid system of solar photovoltaic and diesel generator with the most likely stand-alone systems, i.e. diesel-powered system and solar photovoltaic system, has been analyzed for energy demand through optimization and sensitivity analysis using HOMER. The concept of hybridizing is that the base load is to be covered by largest and firmly available renewable energy source(s), and other intermittent source(s) should augment the base load to cover the peak load. The model has been designed to provide an optimal system configuration based on hour-by-hour data for energy availability and demands. Based on the simulation results, the hybrid system is found to be economically feasible enough to replace the stand-alone system currently practicing to fulfill the energy demand during power cut-off in Nepal.